Wonder cat Kyuu-chan. 4 - Nitori, Sasami (Seven Seas Entertainment, 2022)
Kyuu-chan finds himself embarking on another series of adventures with his human owner, Hinata. First, Hinata has the day off and is ready to spend it relaxing with Kyuu-chan. Next, Kyuu-chan goes to the park to play with some children and is forced to go to the vet. Later, Kyuu-chan searches for a missing sock, and Hinata tries to help Kyuu-chan find some artistic inspiration. Then, Kyuu-chan makes a new friend, and Hinata and Kyuu-chan celebrate a festival.